The Politics of Royal Illness: Real & Feigned - Shah Alam (Universal Journal of History and Culture)
In this article, special emphasis has been laid on the role of mothers. Who had a lot of influence on politics, culture, and society? When a royal woman fell ill, it had many meanings, like Akbar's mother pretended to be ill, after which Akbar went to meet his mother, after which Bairam Khan's reign came to an end. Similarly, whenever a Shah or Sultan fell ill, politics used to start. Like it happened during the times of Alauddin Khilji, Jahangir, and Shah Jahan. Many types of drugs were also used during the Mughal period to prevent motherhood. In this way, Babar's wife, Mubarika Begum, could never become a mother because she was given drugs. When Babar's son Kamran fell ill, he feared that his stepmothers would be poisoned. In this way, the royal illness was sometimes real and sometimes feigned. For example, Malika-i Jahan spread rumors about her son's illness and went to Delhi for treatment and overnight deposed Delhi's Sultan Alauddin Masood and her son. Prince Naseeruddin Mahmood was made the Sultan of Delhi.